Regulation of a DC/DC Boost Converter Under Parametric Uncertainty and Input Voltage Variation Using Nested Reduced-Order PI Observers - Kim, In Hyuk; Son, Young Ik (IEEE transactions on industrial electronics (1982), 2017)
DC/DC boost converters are known for presenting highly nonlinear and nonminimum phase properties. This paper combines a predesigned cascade controller and nested reduced-order proportional-integral observers (PIOs) to maintain the desirable voltage regulation performance of the cascade controller for a dc/dc boost converter subject to load change, parametric uncertainties, unmodeled dynamics, and input voltage variations. In the proposed cascade controller design, the fast inner current loop adopts proportional-integral control and the slow outer voltage loop employs integral-proportional control based on a linearized model at a single nominal operating point. Unified theoretical analysis is performed by applying singular perturbation theory, which confirms the desired approximation of the augmented system with the PIOs to the nominal closed-loop system using the cascade controller without accounting for the uncertainties. The validity of the proposed observer-based control scheme is tested via computer simulations and comparative experiments using a laboratory prototype. Both results show that the closed-loop performance remains nearly nominal under load change, parametric uncertainties, unmodeled dynamics, and input voltage variations, confirming the effectiveness of the proposed controller.